2018
DOI: 10.2174/1381612824666180820144917
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Modulates Body Weight by Reducing Prolactin Via an Adenosine A1 Receptor

Abstract: Cordycepin is an extract from the insect fungus Cordyceps. militaris with various biological function. In previous studies, cordycepin had been reported with excellent anti-obesity effect, but the mechanism is unclear. Evidences also showed that prolactin played an important role in body weight regulation, hyperprolactinemia can promote appetite and accelerate fat deposition. In this study, we explored the molecular mechanism of the anti-obesity effect of cordycepin. In vivo, obese rats model was induced by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Our earlier laboratory studies have found that cordycepin could prevent body weight gain in mice fed high‐fat diets. In this study, we demonstrated that cordycepin could reduce HFD‐induced obesity by regulating the lipid content of droplets in adipocytes …”
Section: Introductionmentioning
confidence: 71%
“…Our earlier laboratory studies have found that cordycepin could prevent body weight gain in mice fed high‐fat diets. In this study, we demonstrated that cordycepin could reduce HFD‐induced obesity by regulating the lipid content of droplets in adipocytes …”
Section: Introductionmentioning
confidence: 71%
“…The effect of cordycepin was also studied in animal models of metabolic diseases, including diabetes and obesity. Cordycepin has been shown to reduce body weight and change fat metabolism in animal models of obesity [ 166 , 238 , 239 , 240 ]. Studies in models of type II diabetes found that cordycepin treatment reduced plasma glucose level, hyperphagia and polydipsia.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a previous study from Ma et al [17] found that a cordycepin treatment of alloxan-induced diabetic mice remarkably reduced the loss of body weight by normalizing the glucose metabolism. But a previous study reported that cordycepin extracted from C. militaris can reduce gains in body weight of mice [30], and a further study indicated that cordycepin modulates the body weight by reducing prolactin via an adenosine A1 receptor [31]. These studies indicate that a reduction in body weight is associated with a lower food intake in DM-treated mice.…”
Section: Plos Onementioning
confidence: 87%